Women Trust Their OBGYNs to Provide Preexposure Prophylaxis: An Opportunity for HIV Prevention - Danvers, Antoinette A.; Chew Murphy, Emma; Avila, Karina; Gonzalez-Argoti, Tatiana; Edwards, Angelic Rivera; Hoffman, Susie; Mantell, Joanne E.; Bauman, Laurie J.; Dolan, Siobhan M. (Frontiers in Reproductive Health, 2022)
Objective: This study aimed to understand how women perceive the role of their Obstetrician and Gynecologist (OBGYN) in screening for and providing preexposure prophylaxis (PrEP) for HIV prevention. Methods: We recruited women ages 18-45 years receiving obstetric or gynecological care at an academic medical center in the Bronx, NY. Thirty participants were enrolled: 10 seeking care for family planning, 10 seeking prenatal care, and 10 seeking care for a sexually transmitted infection. We screened participants for HIV acquisition risk using a PrEP screening tool. We conducted face-to-face, semi-structured interviews, which were audio-recorded, transcribed, and entered into Dedoose for analysis of themes using a grounded theory approach. Results: Sixty percent of the participants were Latinx and 33% African American. Seventy percent had one or more risk factors for HIV acquisition based on the PrEP screening tool, indicating they would benefit from a PrEP discussion. Three main themes emerged from the analysis of interview data. Participants viewed OBGYNs as experts in sexual and reproductive healthcare and believed they were experts in PrEP. Participants were concerned about "PrEP stigma", being judged by their providers as being sexually promiscuous if they expressed a need for PrEP. Lastly, when participants trusted their OBGYN, that trust became a facilitator for women to consider PrEP and offset stigma as a barrier to identifying patients who are candidates for PrEP. Conclusion: Women established in care with an OBGYN are enthusiastic about having access to PrEP services incorporated into their sexual and reproductive healthcare.